Abandoned Places of Adult Education in Canada and Germany - Maren Elfert; Bernd Käpplinger; Suzanne Smythe (Adult Education Research Conference, 2018)
The symposium discusses and compares abandoned places of adult education in Canada and Germany. These are physical (and intellectual) spaces that have been abandoned or moved, or changed its use
Keywords: Adult education; public places; politics of space; neoliberalism; case studies